Spectacle Independence in Patients with Prior Radial Keratotomy Following Cataract Surgery: A Case Series - Agarwal, Smita (Int Med Case Rep J, 2020)
PURPOSE: To assess if post-keratorefractive patients can achieve spectacle independence following cataract surgery with currently available presbyopia correcting intraocular lenses (IOLs). PATIENTS AND METHODS: Retrospective case series of unilateral implantation of the IC-8 IOL in two patients with history of bilateral myopic radial keratotomy (RK) and one patient with history of bilateral myopic RK and astigmatic keratotomy (AK), and bilateral implantation of AT Lisa 939M multifocal IOLs in one patient with previous history of RK and laser in situ keratomileusis (LASIK). RESULTS: Good uncorrected distance, intermediate and near visual acuity (VA) was achieved for most patients. Stereopsis and contrast sensitivity (CS) were maintained in patients that received the IC-8 IOLs, and two patients achieved full spectacle independence. The patient that received the trifocal lenses expressed satisfaction with their vision, but required long distance correction and experienced reduced CS. CONCLUSION: The IC-8 and AT Lisa 939M IOLs both offer satisfactory results and reduced spectacle dependence in post-keratorefractive patients. However, it is recommended to properly counsel visual outcomes and patient expectations before commencing surgery.